Profitability and Firm Size on Firm Value with Intellectual Capital as Moderating Variable on LQ45 Company listed on BEI Period 2018 – 2020 - Vitalis Ari Widiyaningsih; Daniel Budi Pratama; Darmanto Darmanto (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2022)
This study aims to examine the effect of profitability and firm size on firm value and also to determine the effect of intellectual capital as a moderating variable on the relationship between profitability and firm value and firm size on firm value. The population of this study are companies that are members of the LQ45 index for the 2018-2020 period. The sample selection used purposive sampling technique. The data analysis technique used is moderated regression analysis (MRA). This study shows that profitability as measured by ROI has a significant effect on firm value, but GPM as a measure of profitability has no significant effect. Firm size has a positive effect on firm value in LQ45 companies. Intellectual Capital can moderate the relationship between profitability as measured by ROI and GPM. Intellectual Capital also moderates the relationship between firm size and firm value in LQ45 companies for the 2018-2020 period. Keyword: Profitability, Size, LQ45, The Value of the Company, Intellectual Capital